PERTARUNGAN AKTOR DALAM KONFLIK PENGUASAAN TANAH DAN PENAMBANGAN PASIR BESI DI URUT SEWU KEBUMEN - Cahyati, Devy Dhian (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This paper discusses the political ecology conflict in Urut Sewu between various actors. The conflict was caused by iron sand mining in Mirit subdistrict, Kebumen regency. The conflict started from a claim of the land along the southern coast of Kebumen, covering Buluspesantren, Ambal and Mirit subdistricts, was admitted as belonging to armed forces. This claims continued due to the issuance of license on iron sand mining to a company involving military elites. In the conflict, there was a change of problem that was the refusal the military exercises. The results showed that the existing conflict was caused by the interests of managing the natural resources. The conflict was created by elites in order to gain personal benefits by marginalizing the local communities who were highly dependent on the ecology. There were struggles among the state actor, local communities, company and NGO. Key Words: political ecology conflict, elite politic, military, local politic, power